PENGEMBANGAN MEDIA PEMBELAJARAN MIND MAPPING UNTUK MENINGKATKAN MINAT BELAJAR DALAM MATERI KONEKTIVITAS ANTARRUANG KELAS VII SMP PAWYATAN DAHA 1 KEDIRI - Ganang Alkeneza; Sigit Widiatmoko; Heru Budiono (PADMA, 2026)
This study was motivated by the low learning interest of Grade VII students in Social Studies, particularly on the topic of Spatial Connectivity, due to the dominant use of lecture methods and limited instructional media. The study aimed to identify learning problems, develop mind mapping-based learning media, and examine their effectiveness in improving students’ learning interest. This research employed a Research and Development (R&D) approach using the Borg and Gall model, simplified into seven stages. The research involved 11 students in a limited trial and 25 students in a broader field trial. Expert validation indicated that the developed media were feasible for use. The broader field trial showed an increase in the average learning outcome score from 84 (pre-test) to 88.56 (post-test), with a gain of 4.56 points. These findings indicate that the mind mapping-based learning media are feasible and effective in enhancing students’ learning interest and learning outcomes.